The nociceptin/orphanin FQ receptor partial agonist sunobinop promotes non-REM sleep in rodents and patients with insomnia - Whiteside, Garth T; Kyle, Donald J; Kapil, Ram R; Cipriano, Alessandra; He, Ellie; Zhou, Mingyan; Shet, Manjunath S; Hummel, Michele; Knappenberger, Terri; Fukumura, Kazuya; Matsuo, Yoshiyuki; Uehira, Masahiro; et al. (The Journal of clinical investigation, 2024)
Insomnia is a common disorder that poses a significant public health burden. Current treatments for insomnia primarily target aminobutyric acid or orexin signaling, but there is a need for new mechanisms to regulate sleep-wake cycles. Here, Whiteside et al investigate the potential of the nociceptin/orphanin FQ receptor (NOP) system as a treatment for insomnia. They developed a partial agonist called sunobinop and conducted various experiments to assess its pharmacology and pharmacokinetics. In rats, sunobinop decreased wakefulness and increased non-REM sleep, effects that were mediated by NOP activation. In human subjects with insomnia, sunobinop significantly improved sleep efficiency, reduced sleep latency, wake after sleep onset, and nighttime awakenings, and increased perceived sleep quality. The drug was generally well-tolerated with no serious adverse events. These findings suggest that sunobinop, as a NOP agonist, could be a promising treatment for insomnia. Further clinical studies are underway to determine the optimal effective dose.